Предмет: Математика,
автор: annatarukina9
1) (x – 3)(x + 7) - (x + 7)(x – 8) = 0;
2) (4x -9)(x - 2) + (1 - x)(x - 2) = 0;
3) 0,2x (x – 5) + 8(x – 5) = 0;
4) 7(x – 7) - (x – 7)2 = 0.
Ответы
Автор ответа:
5
Ответ:
1) х=-7
2) х₁=2; х₂=
3) х₁=-40; х₂=5
4) х=7
Пошаговое объяснение:
1)(x – 3)(x + 7) - (x + 7)(x – 8) = 0
(x+7)×(x-3-(x-8)) = 0
(x+7)×(-3+8) = 0
(x+7)×5 = 0
5х+35=0
5х=-7
х=-7
2) (4x -9)(x - 2) + (1 - x)(x - 2) = 0
(х-2)×(3х-8)=0
х-2=0 3х-8=0
х₁=2; х₂=
Похожие вопросы
Предмет: Математика,
автор: PlokhovNikita
Предмет: Алгебра,
автор: Chocolate13
Предмет: Физика,
автор: пзилыьпхдрыьре
Предмет: Математика,
автор: рами0208
Предмет: Физика,
автор: daryalobova20